The Failure of Retributive Justice in the Penal Consequence Account of PenalSubstitutionary Atonement - Jansen, Danielle W. (Philosophia Christi, 2025)
The concept of a penal substitute has been the subject of considerable criticism in recent atonement literature as to the internal coherence of the claim that Christ was punished as the substitute for the sinner. However, some penal substitutionary atonement (PSA) defenders have argued that Christ merely endures the penal consequences of human sin rather than suffering punishment (the penal consequence account). In this article, I draw attention to a fundamental problem in the relationship between divine retributive justice and the penal consequence form of PSA and argue that this version of the doctrine fails to satisfy the demands of retributive justice.